Ralph H. Stimson papers - Stimson, Ralph H. (Ralph Humphreys), 1898-1986.
Correspondence, memoranda, reports, notes, printed material, and other papers pertaining chiefly to Stimson's involvement in the League of Nations opium trafficking conferences (1924-1925), his research relating to international organizations, and to the manufacture and international trade of armaments.
Library of Congress Geography and Map Division.
State Department research analyst and armaments expert.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Arms transfers; Drug control -- International cooperation; International agencies; Military weapons; Opium trade; Weapons industry; Armaments experts; Research analysts